Evolutionary Game Theory and the Modelling of Economic Behavior - Gerard van der Laan; A.F. Tieman (Tinbergen Institute, 1996)
Since the 1950's economists applied game theoretical concepts to a wide variety of economic problems. The Nash equilibrium concept has proven to be a powerful instrument in analyzing the outcome of economic processes. Since the late 1980's economists also show a growing interest in the application of evolutionary game theory. This paper discusses the main concepts of evolutionarygame theory and their applicability to economic issues. Whereas traditional game theory focusses on the static Nash equilibria as the possible outcomes of the game, evolutionary game theory teaches us to model explictly the behavior of individuals outside equilibrium. This may provide us with a better understanding of the dynamic forces within a society of interacting individuals.
Keywords: 330